Panaghoy sa suba The call of the river - Montano, Cesar; Plaza, Victoria; Vertido, Cris (CM Films, Inc., 2004)
During the Japanese Occupation in the Philippines, in the island province of Bohol, located in Central Visayas, a banca-operator-turned-guerilla named Duroy (Cesar Montano) fell in love with Iset (Juliana Palermo), a lovely lass from the same village where the people's main thoroughfare is a river. John Smith (Philip Anthony), an American stingy landowner was captured by Iset's beauty as well as Duroy's brother Ibo (Reiven Bulado). Since Ohkohara (Jackie Woo), a handsome Japanese officer takes over in the village; he also falls in love with Iset. During the Japanese Era, Duroy joins a band of guerillas and later becomes their leader mainly because of his talent in creating innovative methods of fighting the enemy. Iset, on the other hand is appalled at the brutality of the Japanese and her father's collaboration with them. She makes a bold move against her parents and what they stand for by joining the guerillas. After a series of sorties, Duroy leads a final assault over the Japanese and succeeded. It boosted love self esteem as an underachiever and illiterate person. What appears to be a battle won in love and in war takes a strange twist in the end with the return of the American suitor. Duroy, after getting rid of the ghost of his troubled and deprived past, decides for everyone else: He answers the insistent call of the river.